Enhancing Graphical Understanding of Statistical Distributions in Physics: Integrating Project-Based Learning with Desmos and Excel: A Case Study of Sixth-Semester Physics Education Students at FKIP Universitas Mataram - Taufik, Muhammad; Hikmawati (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2024)
This study explores the integration of project-based learning with Desmos and Excel to enhance the comprehension of statistical distributions among sixth-semester physics education students at FKIP Universitas Mataram. Employing a mixed-methods approach, combining quantitative assessments with qualitative observations, the research evaluates the effectiveness of Desmos in facilitating statistical understanding within the physics domain. Through structured projects, students engage in data collection, analysis, and interpretation, utilizing Desmos for visualization and exploration of statistical concepts. The findings reveal a significant advantage of Desmos over Excel, with notably higher average scores (85.67 for Desmos compared to 76.33 for Excel) and lower deviation (7.03 for Desmos compared to 8.57 for Excel). This underscores Desmos' efficacy in enhancing students' graphical understanding of statistical distributions. The study underscores the potential of integrating Desmos into project-based learning to cultivate deeper comprehension and engagement in physics education among sixth-semester students at FKIP Universitas Mataram.